Lost cartoons (1930's) : volume 3 - Gillett, Burt; Van Beuren Studios (New York : Goodtimes Entertainment, 2005)
Parrotville post-office -- Ali Baba -- Parrotville old folks -- Simple Simon -- Scottie finds a home -- The hunting season (aka Hunters are coming) -- Spinning mice -- The merry kittens -- The picnic panic.
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Gillett, Burt